Ultrastructural study of liver and lead tissue concentrations in young mallard ducks (Anas platyrhynchos) after ingestion of single lead shot. Issue 3 (1st February 2017) - Pineau, Alain; Fauconneau, Bernard; Plouzeau, Eric; Fernandez, Béatrice; Quellard, Nathalie; Levillain, Pierre; Guillard, Olivier
ABSTRACT: Lead (Pb) represents a serious threat to wildlife and ecosystems. The aim of this study was to examine the subcellular effects of dietary Pb pellet ingestion on mallard ( Anas platyrhynchos ) livers. After ingestion of a single Pb shot (LS4 size class: 0.177 ± 0.03 g) in 41 mallard ducks (22 males and 19 females) versus 10 controls (5 males and 5 females), all 7-week old, a morphologic study was conducted by TEM (transmission electron microscopy) of liver at the subcellular level. The results in treated mallards showed at a magnification of 2500 X that hepatic parenchyma was altered as evidenced by intralysosomal electron-dense deposits, which are compatible with Pb deposits. Further, at a higher magnification (15, 000 X) in both genders, deterioration of mitochondria was observed in which the crests and, to a lesser extent, outer membrane were lysed. While the rough endoplasmic reticulum was fragmented, intracytoplasmic electron-dense material compatible with Pb deposits was maximally visible, thereby underscoring the deeply destructive effect of this metal on the subcellular architecture of the liver. In addition, applying an optimized and validated method in a clean room using electrothermal atomic absorption spectrophotometer (ETAAS) with Zeeman background correction, the objective was to improve and refine certain indispensable measurements pertaining to Pb impregnation in tissues other than liver such as kidneys, bones, and feathers of mallards. Data demonstrated show that compared with controls, Pb accumulation increases significantly, not only in the liver (3-fold), but also in the bones and the feathers (14-fold). No significant difference was noted between males and females. Bearing in mind the marked subcellular toxicity attributed to Pb, this study reinforces present-day arguments advocating limitation of game consumption.